An infectious disease outbreak and increased mortality in wild alpine reindeer. Issue 3 (19th March 2023) - Mysterud, Atle; Viljugrein, Hildegunn; Andersen, Roy; Rauset, Geir Rune; Reiten, Malin Rokseth; Rolandsen, Christer M.; Strand, Olav
Abstract: Climate changes may lead to tipping points where the epidemiological characteristics of infectious wildlife diseases suddenly change, leading to outbreaks. However, empirically documented cases of the extent to which emerging infectious diseases (EIDs) affect populations of large vertebrates are few, partly because of the limited surveillance of remote wildlife populations. EIDs may potentially lead to higher mortality than mean mortality levels. Here, we quantified the likely impact of digital necrobacillosis on the survival and population dynamics of wild alpine reindeer ( Rangifer tarandus ) in Hardangervidda National Park (NP), Norway. The outbreak of digital necrobacillosis in 2019 contributed to a decrease in the summer survival rate of juveniles to 51% compared to an average of 88% in 2005–2018 and 77% in 2020. However, since the outbreak mainly reduced juvenile survival, the impact on short‐term population dynamics was moderate, lowering the population growth rate (λ) before harvest from an average value of 1.18 (2005–2018) to 1.08 (2019) before harvest. In 2019, anomalous climate conditions with a high daily mean temperature combined with the highest recorded daily precipitation in late summer were observed. Further studies are required to document the pathological development of digital necrobacillosis across demographic groups and proximate and ultimate causes of mortality.